2012
DOI: 10.5032/jae.2012.04041
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of North Carolina High School Agricultural Educators Regarding Students with Special Needs Participating in Supervised Agricultural Experience and FFA Activities

Abstract: The purpose of this study was to examine the perceptions of North Carolina high school agricultural educators toward including students with special needs when implementing Supervised Agricultural Experience and participating in FFA activities. The population was all high school agricultural educators in North Carolina with 12 month employment (N = 307). A simple random sample of 172 was selected with a response rate of 45.9%. Participants completed a questionnaire that measured teachers' perceptions and colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Even though the majority of teachers in this study have taken coursework in special education, adequate in-service should be provided so that teachers can stay on top of the research within the special education field. Additionally, there is evidence that teachers who have experienced more in-service opportunities related to inclusion tend to be more willing to include students in other aspects of the agricultural education program, including participation in FFA and SAE (Johnson, Wilson, Flowers, & Croom, 2012). This presents a need for additional training in all areas of the agricultural education program.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the majority of teachers in this study have taken coursework in special education, adequate in-service should be provided so that teachers can stay on top of the research within the special education field. Additionally, there is evidence that teachers who have experienced more in-service opportunities related to inclusion tend to be more willing to include students in other aspects of the agricultural education program, including participation in FFA and SAE (Johnson, Wilson, Flowers, & Croom, 2012). This presents a need for additional training in all areas of the agricultural education program.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both 4-H and agricultural education programs have shown a trend toward positive attitudes by agricultural and extension educators. One investigation of North Carolina agricultural educators working with special needs students when implementing a supervised agricultural experience (SAE) found that teachers reported beneficial outcomes and positive perceptions for students with disabilities (Johnson et al, 2010). A cross-national study with primary and secondary school teachers in South Africa and Finland found overall neutral attitudes toward inclusion (Savolainen et al, 2012).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Considering the benefits students receive from SAE participation, North Carolina teachers believed students with special needs received the same benefits from participation as do other students but identified fewer opportunities for SAE involvement (Johnson, Wilson, Flowers, & Croom, 2012).…”
Section: Benefitsmentioning
confidence: 99%